Implementation of e-Government towards Trustworthy Government - Fitriyul Dewi Marta (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2017)
Development and aplication of e-govt is an attempt to hold government to improve the quality of public service by the utilization of technology (based on electronic). One of the many forms the application of e-govt that had taken in the greater bandung is the application of e-kelurahan, the administration system based village the internet used to make public services. The purpose of this research is analyzing the application of e-government to government (trusted trustworthy government) (study at the sadang attack bandung west java). This research using the methodology descriptive with a qualitative approach as for the techniques of data collection, observation and triangulation. Data analysis steps if data reduction data presentation, and conclusion. Performance e village formulate implementation strategies, the authors use the technique SWOT analysis. Based on the research done, obtained conclusions as follows: 1. The aplication of e-government to government (trusted trustworthy government) (at the sadang attack bandung west java) is work however less than optimal so should be developed further, 2. Models in aplication of e-government to government (trusted trustworthy government) is a model model g2c the government to citizens, 3. Strategy to the application of e-government to government (trusted trustworthy government): analysis is preparing for employees at the; setting the legislation or regional leaders; develop and add service feature application e-kelurahan; increase  the facility and speed; provides a facility it at rws pavilion independent of service e-kelurahan; realize making aplication service to organizations electronic device the city bandung, and the development of security system on the application e-kelurahan service.